Sustainable Supply Chain and its Risk Management: A Systematic Literature Review of Issues and Trends using a Bibliometric and Network Approach - EuiBeom Jeong; Jinsoo Park (International Journal of Supply Chain Management, 2021)
The risks associated with sustainable supply chains (SSCs) have been receiving increasing attention. However, despite increasing research on SSCs, SSC-related risks have not been reviewed satisfactorily or comprehensively. Therefore, we conducted a systematic literature review that incorporated bibliometric, citation network, and keyword network analysis. For this purpose, we selected the top journals in the field of supply chain management and identified 823 related papers in the Scopus database. The analysis revealed the critical issues, topics, and changes over time in research regarding SSC-related risks. Furthermore, we identified specific issues and explored SSC risks via keyword network analysis.